Effectiveness of Turmeric Rhizome Extract and Egg Shell Waste Ointment in Healing Diabetic Wounds in Mice With DDY Strain - Firmansyah, Aryan; Yashuda, Syifana; Hening Hasyyati Husna Pekerti; Jasmine Aprilia Nur Zharifah; Eva Agustin Nurhadiyanti; Fauziningtyas, Rista (Critical Medical and Surgical Nursing Journal, 2025)
Introduction: One of the complications of diabetes is wounds on the feet. The use of curcumin as a natural ingredient can accelerate the healing of diabetic wounds with its anti-inflammatory and antioxidant properties. However, curcumin has low solubility so it requires a conductor such as hyaluronic acid in egg shells to increase hydration and bioavailability. The aim of this research was to determine the effectiveness of turmeric rhizome and egg shell extract ointment in healing diabetic wounds. Methods: True experimental research was carried out using a pre-post test control group design. This research was carried out using 36 mice which were divided equally into 6 control and treatment groups. This study used Kruskal Wallis analysis to determine differences between groups with a significance level used of p<0.05. Macroscopic monitoring by measuring the diameter of the wound and microscopically monitoring the wound using histopathological tests was carried out in this study. Results: The results of macroscopic and histopathological observations showed that the F3 ointment dose group had the best speed of healing diabetic wounds in mice when compared with the other groups. The statistical results significantly show the effect of administering turmeric rhizome and egg shell extract ointment at a p-value of 0.035. Conclusion: Using a combination of turmeric rhizome and egg shell ointment at a dose of 9:15 was proven to be effective in helping speed healing of diabetic wounds in DDY strain mice. This study has the potential to be continued in the next stage by comparing different doses of egg shells so as to create a more effective formulation in healing diabetic wounds.